Crustal shortening, exhumation, and strain localization in a collisional orogen: The Bajo Pequeño Shear Zone, Sierra de Pie de Palo, Argentina. Issue 7 (7th July 2014) - Garber, Joshua M.; Roeske, Sarah M.; Warren, Jessica; Mulcahy, Sean R.; McClelland, William C.; Austin, Lauren J.; Renne, Paul R.; Vujovich, Graciela I.
Abstract The Bajo Pequeño Shear Zone (BPSZ) is a lower‐crustal shear zone that records shortening and exhumation associated with the establishment of a new plate boundary, and its placement in a regional structural context suggests that local‐ to regional‐scale strain localization occurred with progressive deformation. A kilometer‐scale field and analytical cross section through the 80 m thick BPSZ and its adjacent rocks indicates an early Devonian (405–400 Ma) phase of deformation on the western margin of Gondwanan continental crust. The earliest stages of the BPSZ, recorded by metamorphic and microstructural data, involved thrusting of a hotter orthogneiss over a relatively cool pelitic unit, which resulted in footwall garnet growth and reset footwall white mica 40Ar/39Ar ages in proximity to the shear zone. Later stages of BPSZ activity, as recorded by additional microstructures and quartz c‐axis opening angles, were characterized by strain localization to the center of the shear zone coincident with cooling and exhumation. These and other data suggest that significant regional tectonism persisted in the Famatinian orogenic system for 60–70 million years after one microplate collision (the Precordillera) but ceased 5–10 million years prior to another (Chilenia). A survey of other synchronous structures shows that strain was accommodated on progressively narrower structures with time, indicating a regional pattern of strain localization and broad thermal relaxation as the Precordillera collision evolved.